A Critical Guideline Appraisal Overview: Choice Framework for Local Policy and Procedures (Cfpp) 01–06 Decontamination of Flexible Endoscopes 2013 Part 1: Policy and Management and Part 3: Operational Management Manual. Issue 4 (April 2014) - Cobbold, A; Lord, S
Inadequate decontamination of flexible endoscopes potentially exposes patients and staff to pathogenic bacteria and blood borne-viruses. In the UK there have been 176 deaths from definite or probable cases of variant Creutzfeldt-Jakob Disease (vCJD). The peak year of deaths was 2000, since then numbers of cases have fallen (DH 2013a). Effective decontamination removes surface contaminants, organisms and organic matter such as grease or dirt, which may otherwise inactivate the disinfection process (Weston 2008). There are 1134 hospitals listed in the UK (Hospitals Worldwide 2013) of which 215 acute units, 162 independent sector, 49 community units and 6 paediatric units are engaged with Joint Advisory Group in England (JAG 2013). Currently there are several pertinent regulatory British (BS), European (EU) and International (ISO) decontamination standards which are intended to prevent contact transmission and environmental contamination. The Department of Health aims to empower individual departments to be more proactive in their own local decision-making processes by setting standards in the form of CFPP 01–06 (DH 2013a).